Improvement of Initial Reading Skills through Analytical and Synthetic Structural Methods (SAS) in Grade 1 SD Inpres Timbuseng with Literature Study - Perawati Bte Abustang; Jusmawati Jusmawati; Mutmainna Mutmainna; Yandika Putra; Fransiska Falentina Asa; Kristin Lestari (Universitas Muhammadiyah Enrekang, 2024)
The aim of this research is to find the main themes and categories of research on improving beginning reading abilities through analytical and synthetic structural methods. Data taken to fulfill the objectives of this research, the author conducted a search from several relevant sources from Google Scholar. Articles are determined by four combinations of keywords, then the articles are included in the data set, researchers apply analytical and synthetic structural methods (SAS). The articles that will be the source of the research are limited to the last five years. The dominant research methodology of the articles reviewed is qualitative. The four main themes revealed from the qualitative content analysis are: SAS method, causes of initial reading ability using the SAS method, cases of initial reading ability using the SAS method, solutions to overcome initial reading ability using the SAS method. Articles are filtered starting from topic description, eligibility criteria and search strategy. The total of articles studied was 15 from different sources. Then review it again according to the theme in the title obtained. The reason why children are less interested in reading is first and foremost because parents are not aware of the importance of reading from an early age. Second, the books in the school library are less interesting, have no pictures, and are not colored according to the child's preferences. Third, public interest in establishing environmental reading parks is very low, even though good reading can improve students' academic achievement. One of the factors causing students' difficulties in reading is the use of methods in learning activities. The solution offered by the teacher is to use several methods and learning media that are appropriate to the child's condition. The main steps taken by researchers when applying the SAS method include dividing sentences into several words, dividing words. into several syllables, dividing syllables into letter sounds, and combining letter sounds into syllable sounds and sound combinations as many as syllables.